MAGNITUDE DA TUBERCULOSE NA ROTA BIOCEÂNICA: UMA ANÁLISE EPIDEMIOLÓGICA - CUNHA, João Pedro Arantes da; MARQUES, Ana Maria Campos; MACIEL, Ruberval Franco; CAMPOS, Rafael Vilela de; KOWALSKI, Paloma Almeida (ANAIS DO ENIC, 2022)
-